2013
DOI: 10.1007/s00213-013-3294-3
|View full text |Cite|
|
Sign up to set email alerts
|

Time-dependent decreases in nucleus accumbens AMPA/NMDA ratio and incubation of sucrose craving in adolescent and adult rats

Abstract: Rationale and objectiveThere is evidence that cue-induced sucrose seeking progressively increases after cessation of oral sucrose self-administration (incubation of sucrose craving) in both adolescent and adult rats. The synaptic plasticity changes associated with this incubation at different age groups are unknown. We assessed whether incubation of sucrose craving in rats trained to self-administer sucrose as young adolescents, adolescents, or adults is associated with changes in 2-amino-3-(3-hydroxy-5-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 59 publications
3
63
0
Order By: Relevance
“…It is well established that extended drug access causes different physiological and behavioral changes than limited drug access (Ahmed and Kenny, 2011; Koob and Le Moal, 2001). Additionally, there is evidence from incubation of reward-craving studies that adult-onset selfadministration is associated with different physiological and behavioral changes than juvenile-and adolescent-onset selfadministration (Counotte et al, 2014;Doherty et al, 2013;Li and Frantz, 2009). …”
Section: Methodological Considerationsmentioning
confidence: 93%
“…It is well established that extended drug access causes different physiological and behavioral changes than limited drug access (Ahmed and Kenny, 2011; Koob and Le Moal, 2001). Additionally, there is evidence from incubation of reward-craving studies that adult-onset selfadministration is associated with different physiological and behavioral changes than juvenile-and adolescent-onset selfadministration (Counotte et al, 2014;Doherty et al, 2013;Li and Frantz, 2009). …”
Section: Methodological Considerationsmentioning
confidence: 93%
“…Adolescent rats started sucrose self-administration at postnatal day (P)35, while adult rats were P70 when self-administration training started. Note that the group that was called “Young adolescents” in our previous paper (Counotte et al, 2014) is now called “Adolescents” as we decided to only look in the two extreme groups in the present study. Rats were housed two per cage under reversed lighting conditions (lights on at 7PM) for the duration of the sucrose self-administration experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescence is a period of continued brain development (Casey et al, 2010, Counotte et al, 2011b, Blakemore and Robbins, 2012) which renders individuals with different reward sensitivity and altered long-lasting consequences of exposure to rewards compared to reward exposure during adulthood (Counotte et al, 2011a, Counotte et al, 2014). Previously, we showed that time-dependent increases in cue-induced sucrose seeking (incubation of sucrose craving) were more pronounced in adult rats that started self-administration at postnatal day (P)70 compared to adolescent rats that started at P35 (Counotte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations